Arte urbana, política e escola: um diálogo possível - Débora Cristina da Cunha Souza (2018)
This article deals with some of the anxieties present in my trajectory as teacher and graffiti artist, of the possibilities of dialogues between graphite and teaching/learning in Art. I follow paths that intertwine my teaching life and the urban environment, aligned with the cultural baggage of students in the classroom. This artistic and teaching trajectory helped me in the pedagogical process, allowing a greater dialogue between students and Art and the proposal of Graffiti as a possibility to expand this artistic and teaching work.